2020
DOI: 10.1002/smr.2267
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of source code metrics and smart contract resource consumption

Abstract: A smart contract (SC) is a programme stored in the Ethereum blockchain by a contract-creation transaction. SC developers deploy an instance of the SC and attempt to execute it in exchange for a fee, paid in Ethereum coins (Ether). If the computation needed for their execution turns out to be larger than the effort proposed by the developer (i.e., the gasLimit), their client instantiation will not be completed successfully. In this paper, we examine SCs from 11 Ethereum blockchain-oriented software projects hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
8
0
2
Order By: Relevance
“…Transaction fees in the Ethereum blockchain are called gas, which is the cost necessary to perform a transaction by miners. A transaction involving complex smart contract execution can have higher prices than an ordinary Ether transaction [104]. Miners can set the minimum gas price and decline to process a transaction if it does not meet their price threshold.…”
Section: Other Collective Patternsmentioning
confidence: 99%
“…Transaction fees in the Ethereum blockchain are called gas, which is the cost necessary to perform a transaction by miners. A transaction involving complex smart contract execution can have higher prices than an ordinary Ether transaction [104]. Miners can set the minimum gas price and decline to process a transaction if it does not meet their price threshold.…”
Section: Other Collective Patternsmentioning
confidence: 99%
“…They presented the most used and least used opcodes measures irrespective of their relationship with the increase in gas consumption. The study suggested that the association of gas consumption and the various opcodes and source code parameters should be determined.Ajienka et al 25 conducted an empirical analysis of the smart contract resources consumption and different source code metrics. Their results showed a significant correlation between object-oriented programming metrics and gas consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Transaction fees in the Ethereum blockchain are called gas, which is the cost necessary to perform a transaction by miners. A transaction involving complex smart contract execution can have higher prices than an ordinary Ether transaction [99]. Miners can set the minimum gas price and decline to process a transaction if it does not meet their price threshold.…”
Section: Other Collective Patternsmentioning
confidence: 99%